2000
DOI: 10.1159/000055938
|View full text |Cite
|
Sign up to set email alerts
|

Ontogeny of Pig Discrete Peyer’s Patches: Distribution and Morphometric Analysis

Abstract: We investigated the development of lymphoid and non-lymphoid cells in discrete Peyer’s patches (PP) of the pig using immuno-histology and image analysis. In newborn piglets discrete PP were mainly populated by CD2+, CD3+ T cells, and major histocompatibility complex class II+ cells, many of which were of macrophage and dendritic cell lineage. Four days after birth, cells were localized in defined regions: the follicle; the inter-follicular area and the dome region. Compartmentalization within the follicle star… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 28 publications
0
31
0
Order By: Relevance
“…In pigs the structure of the Peyer's patches, under various antigenic stimuli, has been described [7,26,29], and the appearance of lamina propria and intraepithelial lymphocyte subpopulations have been analysed [32,34,43]. To analyse these various methods to isolate lymphocytes and dendritic cells from the intestine have been developed [2,18,19,33,39].…”
Section: Gut Function and Immunitymentioning
confidence: 99%
See 1 more Smart Citation
“…In pigs the structure of the Peyer's patches, under various antigenic stimuli, has been described [7,26,29], and the appearance of lamina propria and intraepithelial lymphocyte subpopulations have been analysed [32,34,43]. To analyse these various methods to isolate lymphocytes and dendritic cells from the intestine have been developed [2,18,19,33,39].…”
Section: Gut Function and Immunitymentioning
confidence: 99%
“…Unlike the mature pig [43,47], where there is a high degree of organisation, it has been shown that the cells and structures involved in mucosal immune responses are initially absent at birth and populate the intestine of the young pig in a highly programmed sequence [26,32,44]. To date four phases to this process have been identified:…”
Section: Development Of Mucosal Immunological Architec-turementioning
confidence: 99%
“…These interfollicular areas have been reported to include T cells, interdigitating dendritic cells, and macrophages [29]. Therefore, TLR2 + or TLR9 + cells in the interfollicular area may play a crucial role in the activation of the immune system in presuckling newborns.…”
Section: Discussionmentioning
confidence: 99%
“…These follicles have been reported to consist of T cells, B cells, lymphoblasts, follicular dendritic cells, and macrophages [29]. In addition, both TLR2…”
Section: Discussionmentioning
confidence: 99%
“…The gut-associated lymphoid tissue (GALT) comprises follicles or groups of them defined as Peyer's patches, surrounded by specialised M cells, responsible for the transport in the patches of antigens and bacteria coming from the intestinal lumen [44,57,77]. The GALT also includes diffuse lymphoid tissue in the lamina propria, intraepithelial lymphocytes, mesenteric lymph nodes and an appendix.…”
Section: Mucosal Immunitymentioning
confidence: 99%